2011
DOI: 10.1016/j.cub.2011.03.007
|View full text |Cite
|
Sign up to set email alerts
|

A Molecular Pathway for Myosin II Recruitment to Stress Fibers

Abstract: These experiments identified a pathway, involving Dia2- and Arp2/3-promoted actin filament nucleation and several functionally distinct tropomyosins, that is required for generation of contractile actomyosin arrays in cells.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

27
346
2

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 252 publications
(375 citation statements)
references
References 50 publications
27
346
2
Order By: Relevance
“…Indeed, forcing the mitotic and interphase formins to switch location, led to a corresponding switch in the acetylated state of Tpms within each actin-Tpm polymer, which -in turn -was shown to redirect the location of the myosin motors in the cell (Johnson et al, 2014). This aligns well with the observation that the formin Dia2 may be responsible for recruiting Tpm4.2 in an isoform-specific manner to actin filament arcs in U2OS cells, which, in turn, appears to recruit MyoIIA to these filaments (Tojkander et al, 2011). Thus, formins have been shown to play a key role in determining the Tpm composition and physical properties of an actin polymer.…”
Section: Assembly Of Specific Tpms Into Actin Filamentssupporting
confidence: 70%
See 1 more Smart Citation
“…Indeed, forcing the mitotic and interphase formins to switch location, led to a corresponding switch in the acetylated state of Tpms within each actin-Tpm polymer, which -in turn -was shown to redirect the location of the myosin motors in the cell (Johnson et al, 2014). This aligns well with the observation that the formin Dia2 may be responsible for recruiting Tpm4.2 in an isoform-specific manner to actin filament arcs in U2OS cells, which, in turn, appears to recruit MyoIIA to these filaments (Tojkander et al, 2011). Thus, formins have been shown to play a key role in determining the Tpm composition and physical properties of an actin polymer.…”
Section: Assembly Of Specific Tpms Into Actin Filamentssupporting
confidence: 70%
“…Studies on cultured human osteosarcoma cells revealed that they express at least five Tpm isoforms that are functionally nonredundant; depletion of any one of these isoforms led to drastic defects in stress fiber assembly and/or myosin II recruitment (Tojkander et al, 2011). The Tpm isoforms also display partially distinct localization patterns within the stress fiber network, suggesting that they specify the different actin filament populations that are needed for stress fiber assembly (Fig.…”
Section: Role Of Tpm-containing Filaments In Cytoskeletal Structuresmentioning
confidence: 99%
“…In the first case, FAs were isolated and did not occupy the whole pattern ridge or groove (figure 8e). Actin fibres connected to these FAs resembled uncontractile dorsal stress fibres [32], whereas longitudinal FAs were anchored to thicker and contractile ventral stress fibres. Therefore, on 5 mm patterns, the establishment of transverse adhesions is admissible, but their maturation is unfavoured with respect to FAs growing along the pattern.…”
Section: Discussionmentioning
confidence: 99%
“…myosin, α-actinin and tropomyosin), which often have specialized functions (Quick and Skalli, 2010;Tojkander et al, 2011;Wang et al, 2011). There are differences in the biochemical and biophysical properties (e.g.…”
Section: Cellular Functions Of the Contractomementioning
confidence: 99%
“…Several F-actin-binding proteins, most notably tropomyosin, inhibit binding of myosin to the actin filament through steric hindrance, such that even the assembled actomyosin structure is not capable of generating contractility unless tropomyosin shifts its position along the filament (von der Ecken et al, 2014). A number of tropomyosin isoforms have a positive role in recruiting myosin to stress fibers (Tojkander et al, 2011). The F-actin-severing protein cofilin 1 has also been shown to compete with myosin for binding sites on F-actin (Wiggan et al, 2012).…”
Section: Contractome Subnetworkmentioning
confidence: 99%